Pembuatan Sistem Informasi Desa (SID) untuk Menunjang Pelayanan di Desa Klangon, Madiun: Village Information System Set Up in Klangon Village, Madiun, to Support Services - Nashrul Millah; Miswanto Miswanto; Cicik Alfiniyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The quality of village services provided to the community can be raised with the implementation of an effective information system. Klangon Village, Saradan District, Madiun Regency, is the program's partner. Due to a lack of information system management skills, the Village Information System has not been implemented in an ideal manner.An alternative solution offered is to provide training and assistance to local government staff in Klangon village to develop and manage Information Systems. The process starts with a partner survey to identify the underlying causes of the issue at hand, followed by training, mentorship, and program evaluation. The outcomes of this civic engagement project include the creation of a website serving as the village's information system and an improvement in the village of Klangon's capacity to maintain it.